Manipulative Discursive Strategies in Facebook Posts of Failed Online Ponzi Schemes a Study of Investment Narratives (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2025)
This study investigates manipulative discursive strategies employed in Facebook posts of some failed Nigerian Ponzi schemes disguised as business entities between 2020 and 2021. Previous language studies (Chiluwa & Chiluwa (2022), Chiluwa, Kamalu & Anurudu (2020), Onanuga & Taiwo (2020)) on the proliferation of Ponzi schemes on social media focused on the famous Mavrodi Mundial Moneybox (MMM), iCharity, ultimate cycler and Loom, therefore the present study expands the scope by including other schemes like MBA Forex, Barimike Group, Chinmark/FinAfrica Investment and Ovaioza Food Produce and Storage Business (OFPSB). The research adopts a descriptive approach to identify and analyse manipulative discursive strategies used to attract potential clients, foster trust, and encourage financial engagement. Data were purposively collected from eight promotional posts made by four businesses/investment schemes —MBA Forex, Barimike Group, Chinmark Group and OFPSB and analysed using Ruth Wodak’s Discourse Historical Approach (DHA). The analysis reveals recurrent manipulation strategies, including rebranding of investment schemes as business partnership, promise of high returns on investment with no risk, use of exaggerated figures for legitimization, fear tactic, trust framing, false proof, scarcity framing, temporal urgency, and pseudo authority through quotations. These tactics are often employed to create an illusion of safety, inclusivity, and inevitability of profit. The study concludes that online investment discourse blends interpersonal rapport-building with subtle pressure to influence audience decision-making.
Keywords: manipulative discursive strategies, Ponzi scheme, discourse historical approach, online investments